A Comparative Perspective on Legal and Clinical Reasonings - Carole Senechal (Comparative Legilinguistics)
The increasing encounters of clinical science and the rule of law in and outside the courtrooms is one distinctive characteristic of our modern era. At first glance, legal analysis and clinical reasoning could be either completely different or substantially similar. Should we consider the issue through the lens of our scientific revolution legacy, a common rational framework would be a defining converging point drawing together a step-by-step analysis from proven or known facts to the applicable standards, whether it be of law or medicine. However, key differences cannot be overlooked between two disciplines which purport to answer different sets of “what is” vs “should be” questions. This text provides an in-depth comparative analysis of the premises and processes underlying both the legal and clinical reasonings. It highlights cultural differences between the two disciplines which extend beyond the need to translate between two distinct languages, that of law and of medicine. Rather, it can be fairly stated that a court trial involving medical expertise should be ordering a fair and structured translating process between legal and medical cultures.